(untitled) (Texas Journal of Engineering and Technology, 2022)
A crucial and important input component for constructing a geomechanical model and estimating wellbore failure is the magnitude of the in-situ stresses (vertical stress, and minimum and maximum horizontal stresses). In this study, the field case was conducted to calculate the in-situ stresses for the area of interest that extended from the Sadi to Zubair formations in order to reduce the issues that were associated during activities. To achieve the purpose of this study, the prevalent data in the area of interest was gathered and checked. Then, the mechanical rock properties, hydrostatic pressure, and formation pore pressure were computed to construct the profiles of the in-situ stresses. Finally, the magnitude of the in-situ stresses is important to decrease the problems that are associated with drilling and production operations.